Higher Education Marketing Strategy in Increasing the Number of Students (Case Study of Budi Darma University) - Sianturi, Ronda Deli (Journal Boas : Business, Economics, Accounting And Management, 2023)
To find out the marketing strategy of higher education in increasing the number of prospective new students in each academic year, with research locations at Budi Darma University. Market competition in the world of education is getting tougher, so it requires a marketing strategy in recruiting new students. To ensure that the Budi Darma University College is in demand by prospective students who will enter higher education, the marketing strategy implemented is to instill confidence in students that the college they enter is the right college to continue their studies to a higher level. The subject of this research is the New Student Admissions Committee (PMB), Academic and Student Affairs Section of Budi Darma University, This research uses a descriptive research type and a qualitative approach with data sources obtained from primary and secondary data that are relevant to the problems studied. Data collection techniques were used by means of observation, interviews and documentation, while the data analysis techniques used were data reduction, data presentation and data verification. The results that can be seen from the higher education marketing carried out by Budi Darma University are the increasing number of new students entering Budi Darma University every new academic year. The constraints faced from the marketing of these tertiary institutions, where there are more and more private tertiary institutions that are standing,